The integration of ICT tools for collaborative partners selection / Noor Azliza Che Mat, Noor Maizura Mohamad Noor and Rosmayati Mohemad - Che Mat, Noor Azliza; Mohamad Noor, Noor Maizura; Mohemad, Rosmayati (Faculty of Information Management, 2022)
Due to rising competition in global marketplaces, it is necessary to select appropriate partners to build Collaborative Networks (CNs). Partner selection based on partner-related characteristics is difficult to quantify due to the difficulty of giving a numerical value to these variables. Furthermore, present frameworks for partner selection do not make use of the benefits of DSS and ICT technologies. As a result, developing an ICT-based partner selection strategy before establishing the collaborative network is essential for operating a successful and effective collaborative network. This study provides a significant implication to the DSS domain as the framework embeds a model of partnerrelated selection criteria by utilizing the ICT tools in evaluating partner selection criteria.